Arabic Speaking Learning: A Suitable Method Can Be Used By Teacher - Muhlasin; Umi Rofingah (The Progress: Journal of Language and Ethnicity, 2022)
This paper aims to provide an overview of improving speaking skills (Maharah Al-Kalam) in learning Arabic through the presentation of methods and learning techniques, according to experts, which aims to make it easier for Arabic language educators to teach Arabic language skills with creative methods. In the context of learning Arabic. The reason for conducting this research is due to the low ability of students to master the language skills while learning Arabic at school. The research method that the authors used in this study, based on the sources studied, was library research. The results of the study stated that students were equipped with basic speaking skills to improve speech proficiency, such as practicing the application of dialogue patterns, vocabulary, rules, facial expressions, and so on. Several techniques might be used in this exercise, including dialogue (Al-Hiwar), pattern practice (Tathbiq Al-Namudzaj), and oral essays (Al-Tarkib Al-Syafawi). Of the several methods of learning language skills presented in this paper, according to the researcher, the most suitable method used in learning speaking skills is the direct method.